Pemanfaatan Sampah Plastik Menggunakan Metode Ecobrick Menjadi Meja - Sevia Dwi Astuti; Widyanur Handari; Siti Sahara (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Plastic is always present in everyday life because of its extraordinary durability. Plastics offer a number of benefits, including light weight, their ability to act as insulators, their resistance to degradation, and their relatively low production costs. The use of plastic has become an integral part of everyday life, covering various aspects ranging from household appliances to packaging for food and drinks. As a result, plastic waste is increasing and becoming more difficult to manage. The solution to this problem is by making ecobrick products, which can be made easily, with tools and materials that are easy to obtain. The aim of this service is to increase public awareness, especially in the Pondok Ungu Permai Housing area, Bahagia Village, Babelan District, Bekasi Regency regarding ecobrick products as a step towards caring for the environment in order to create a clean and healthy environment. The method used is counseling in the form of lectures and demonstrations. The results obtained are that the community can understand the importance of maintaining a clean and healthy environment by sorting waste properly, and is able to provide ecobrick products in the form of chairs, both for personal and community needs.